Complement Component C1q Programs a Pro-Efferocytic Phenotype while Limiting TNFα Production in Primary Mouse and Human Macrophages - Hulsebus, Holly J.; O’Conner, Sean D.; Smith, Emily M.; Jie, Chunfa; Bohlson, Suzanne S. (Frontiers in Immunology, 2016)
Deficiency in complement component C1q is associated with an inability to clear apoptotic cells (efferocytosis) and aberrant inflammation in lupus, and identification of the pathways involved in these processes should reveal important regulatory mechanisms in lupus and other autoimmune or inflammatory diseases. In this study, C1q-dependent regulation of TNFα/IL-6 expression and efferocytosis was investigated using primary mouse bone marrow derived macrophages, and human monocyte derived macrophages. C1q downregulated LPS-dependent TNFα production in mouse and human macrophages. While prolonged stimulation with C1q (18 hours) was required to elicit a dampening of TNFα production from mouse macrophages, the human macrophages responded to C1q with immediate downregulation of TNFα. IL-6 production was unchanged in mouse and upregulated by human macrophages following prolonged stimulation with C1q. Our previous studies indicated that C1q programmed enhanced efferocytosis in mouse macrophages by enhancing expression of Mer tyrosine kinase and its ligand Gas6, a receptor-ligand pair that also inhibits proinflammatory signaling. Here we demonstrated that C1q-dependent programming of human macrophage efferocytosis required protein synthesis, however neither Mer nor the related receptor Axl were upregulated in human cells. In addition, while the C1q-collagen-like tails are sufficient for promoting C1q-dependent phagocytosis of antibody coated targets, the C1q-tails failed to program enhanced efferocytosis or dampen TNFα production. These data further elucidate the mechanisms by which C1q regulates proinflammatory signaling and efferocytosis in macrophages, functions that are likely to influence the progression of autoimmunity and chronic inflammation.